Keringkam's: starter kit / Muhamad Rusyaidi Sanidi - Sanidi, Muhamad Rusyaidi (Faculty of Art and Design, 2020)
Research on material culture usually related to artefacts which are often involved in beliefs, value, idea and the characteristics of a community.